1985
DOI: 10.1007/bf02916564
|View full text |Cite
|
Sign up to set email alerts
|

Retention of cadmium in organs of the rat after a single dose of labeled cadmium-3-phytate

Abstract: Because of the low safety factor estimated for the normal content of Cd in human foods, it is important to establish the influence of food constituents such as phytate on the bioavailability of this toxic metal. We studied the retention of radioactive(109)Cd administered to rats as a chloride or a phytate in a single dose by stomach tube. The animals were fed either a normal rat chow containing 0.29% of phytate or a low phytate diet containing less than 0.1% phytate. Highly elevated levels of(109)Cd were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…Generally, Cd absorption is enhanced when dietary concentrations of Ca, Fe and Zn are low (Flanagan et al 1978;Jacobs et al 1978;Kello et al 1979;Kostial et al 1980;Hoadley & Cousins, 1985;Schümann et al 1990;McKenna et al 1992;Wing et al 1992;Reeves & Chaney, 2001). In addition, increased intake of phytate and some dietary fibres appears to depress Cd uptake (Kiyozumi et al 1982;Jackl et al 1985;Lind et al 1998), but increased intake of protein appears to enhance Cd absorption and retention (Schäfer et al 1986;Kimura et al 1998). In our present study, dietary amounts of essential nutrients, except for Zn, were provided at or near recommended levels (National Research Council, 1995).…”
Section: Cadmium Absorption and Retentionmentioning
confidence: 78%
See 2 more Smart Citations
“…Generally, Cd absorption is enhanced when dietary concentrations of Ca, Fe and Zn are low (Flanagan et al 1978;Jacobs et al 1978;Kello et al 1979;Kostial et al 1980;Hoadley & Cousins, 1985;Schümann et al 1990;McKenna et al 1992;Wing et al 1992;Reeves & Chaney, 2001). In addition, increased intake of phytate and some dietary fibres appears to depress Cd uptake (Kiyozumi et al 1982;Jackl et al 1985;Lind et al 1998), but increased intake of protein appears to enhance Cd absorption and retention (Schäfer et al 1986;Kimura et al 1998). In our present study, dietary amounts of essential nutrients, except for Zn, were provided at or near recommended levels (National Research Council, 1995).…”
Section: Cadmium Absorption and Retentionmentioning
confidence: 78%
“…Others (Wing, 1993;Lind et al 1998) attributed decreased Cd absorption in animals fed wheat bran to the presence of phytate or fibre in the bran. In addition, Jackl et al (1985) reported that phytate markedly depressed Cd absorption in rats. Some dietary fibres have also been reported to depress Cd absorption (Kiyozumi et al 1982).…”
Section: Cadmium Absorption and Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a possible explanation for the reduced cadmium accumulation in the rats that were fed the calcium‐enriched diets may be a decrease in the cadmium binding activity due to a competitive interaction at the CaBP accompanied by a decrease in the mucosal cadmium uptake ( Breddermann and Wassermann, 1974). Furthermore, the effects might be due to the beneficial effect of PA concerning absorption and retention of cadmium ( Jackl et al, 1985) as well as antagonistic Ca—Cd‐interactions ( Rambeck, 1994; Rambeck and Guillot, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant difference (p≤0.05) in the concentrations of total protein, bilirubin , creatinine, inorganic phosphate and haemoglobin in both the test and control rabbits. Table 4 revealed that there was elevated total cyanide contents in the (Jack et al, 1985;McCane and Woddowson, 1953). Cyanogenic glycosides are precursors of hydrogen cyanide, a well known natural toxicant in foods.…”
Section: Resultsmentioning
confidence: 99%